The previously unknown pupa and adult male of Neobezzia fittkaui wirth & Ratanaworabhan (Diptera, Ceratopogonidae) - Ronderos, María Marcela (2011)
The previously unknown pupa and adult male of Neobezzia fittkaui Wirth & Ratanaworabhan (Diptera, Ceratopogonidae). The pupa of Neobezzia fittkaui Wirth & Ratanaworabhan, 1972, collected from a mat of floating fern (Salvinia auriculata Aubl., Salviniaceae) in Ilha da Marchantaria near Manaus, Brazil and the reared adult male are described, photographed and illustrated for the first time. This is the first detailed pupal description for the genus Neobezzia Wirth & Ratanaworabhan.